Bioelectrical impedance analysis of body composition and muscle mass distribution in advanced kayakers - Rynkiewicz, M.; Rynkiewicz, T. (Human Movement, 2010)
Purpose. The study aims at assessment of body composition and muscle mass distribution in advanced kayakers. Kayak paddlers should be characterized by large body mass with a significant percentage of muscle mass, especially in the trunk region. Basic procedures. The sample consisted of 26 kayakers. The body composition and muscle mass distribution were determined based on bioelectrical impedance analysis. Main findings. The subjects had large muscle mass and average fat mass. The percentage of body fat mass in the kayakers was observed to increase with age, whereas the muscle mass percentage decreased, with the exception of the limbs. Conclusions. BIA of body composition and distribution of muscle mass should be a standard diagnostic method to collect data on proper adaptation of kayakers to their training programs.